A nacionalização de escolas teuto-brasileiras-evangélicas no sul do Brasil : entre adesões e resistências (1937-1945) - Figueiredo, Milene Moraes de (2022)
The present study analyzes the impact of the policy of nationalization of education in the south of Brazil, in the New State period, in German-Brazilian-Evangelical schools from the case of two educational institutions: Colégio Evangélico Alberto Torres (Lajeado), Colégio Evangélico Augusto Pestana (Ijuí). Founded in 1892 and 1899, respectively, constituted as German-Brazilian-Evangelical institutions in the midst of a complex and conflicting process of (re)Germanization of German immigrants, who settled in southern Brazil after the Proclamation of the Republic, which walked side by side, with the simultaneous attempt to assimilation of immigrants by the Brazilian government, which reached its apex in the New State. The schools had their foundations related to the Evangelical Communities of their respective municipalities, and, later, they were linked to the Riograndense Synod, being until today integral schools of the Sinodal Network. They had their faculty, students and administrative staff composed mainly of German immigrants (or German-speaking) and descendants. The German language, conceived as a way of bringing Evangelicals-Lutherans closer to God through reading the Bible, was the main language used in everyday school life. With the implementation of the policy of nationalization of education, during the New State, schools could no longer maintain this structure, as both the source language and the teaching materials in German were prohibited, the directors should be born Brazilians, as well as the teachers of Portuguese, History of Brazil and Geography, which came to be considered nationalization subjects. Schools went through great difficulties in this period, needing to make a series of changes to adapt and keep their doors open. Believing that it is not possible to make such drastic changes, even more so abruptly and quickly, we question what strategies were found to survive this period and whether the schools or the subjects who inhabited them found some form of confrontation, disobedience or even resistance. to homogenizing policies so as not to completely ignore the language and elements of German culture that were integral parts of its institutional identity. The time frame covers the period from 1937 to 1945. The analysis is based on theoretical-methodological assumptions and History of Education, with some approximations to the Conceptual History of Politics. The concepts of school culture and resistance are mobilized as research tools. The first is worked from the perspectives of Dominique Julia, Escolano Benito, Viñao Frago and Justino Magalhães. The concept of resistance is taken from the perspectives of Pierre Ansart, James Scott, Jácques Sémelin, Denise Rollemberg, Pierre Laborie, Gene Sharp, Frédéric Gros. between others. This had an important role in defining the four categories of analysis used in the research: adherence, confrontation, disobedience and resistance. The analyzed sources mainly comprise documents related to the Empirical Culture of the schools (documents produced and/or safeguarded by the institutions, such as correspondence, inspection reports, school notebooks, memorialistic works, among others), but they are also used as supplementary sources, documents related to the Academic Culture of the schools and the Riograndense Synod (articles, final works, dissertations, theses, among others) and documents of the Political Culture of the School (legislation of the period). The research results showed that there was mainly a demonstration of adherence to this period, but it was not a voluntary adherence, but a submission imposed in a context of hierarchy and unbalanced relationship of forces. There were also timid signs of confrontation, disobedience on the part of the students and resistance that manifested itself through a hidden speech, aiming at the maintenance of the German language. Therefore, schools were nationalized, but it was a complex process marked by ambivalent actions, despite the predominance of adhesion.